1987
DOI: 10.3758/bf03204959
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for distinct serial processes in animals: The multiplicative-factors method

Abstract: The assumption that responses are controlled by distinct serially arranged processes was used by Sternberg (1969a) to explain the result, observed in many human experiments, that two factors have additive effects on reaction time (RT). With slight changes, Sternberg's explanation of additive factors with RT also explains the result, observed in animal experiments, that two factors have multiplicative effects on response rate. This article describes and interprets 17 examples of multiplicative factors from resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
23
0

Year Published

1995
1995
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 118 publications
1
23
0
Order By: Relevance
“…For example, Becker (1979) investigated the effects of word frequency (high vs. low frequency) and semantic context (related vs. unrelated context) on word recognition and reported that word frequency interacts with semantic context. This suggests that word frequency and semantic context influence a common stage.Following this early classic work, demonstrations of clear additivity have been observed across diverse studies (see Sternberg, 1998, for an extensive review; see also Roberts, 1987;Sanders, 1990), supporting the claim that additive effects reflect discrete stages of processing and that different factors can selectively influence these stages. Given that the notion of discrete stages seems simplistic and architecturally implausible, it is perhaps unsurprising that additive-factor logic has encountered some resistance and skepticism (e.g., Broadbent, 1984, pp.…”
mentioning
confidence: 81%
“…For example, Becker (1979) investigated the effects of word frequency (high vs. low frequency) and semantic context (related vs. unrelated context) on word recognition and reported that word frequency interacts with semantic context. This suggests that word frequency and semantic context influence a common stage.Following this early classic work, demonstrations of clear additivity have been observed across diverse studies (see Sternberg, 1998, for an extensive review; see also Roberts, 1987;Sanders, 1990), supporting the claim that additive effects reflect discrete stages of processing and that different factors can selectively influence these stages. Given that the notion of discrete stages seems simplistic and architecturally implausible, it is perhaps unsurprising that additive-factor logic has encountered some resistance and skepticism (e.g., Broadbent, 1984, pp.…”
mentioning
confidence: 81%
“…17 For any level G k of G, the p.eect on M AB of a factor F with two levels F 1 Y F 2 is the value of the measure when F F 2 divided by its value when F F 1 . 18 As shown by Anderson (1996) and Roberts (1987), analyses of such data bene®t from numeric scaling of the factor levels; see Sections 13,15,and Appendix A.15. and Appendix A.9.1. However, factorial experiments are essential with composite measures, because the predictions take the form of statements about how factor eects combine.…”
Section: Factorial Experimentsmentioning
confidence: 99%
“…In Appendix A.15 I discuss a similar numerical scaling of factor levels (but one that linearizes their main eects on the untransformed RR data) and explain how Roberts (1987) used this representation to help discriminate among the simple multiplicative model of Eq. (4) and the three hybrid models expressed by Eq.…”
Section: Commentsmentioning
confidence: 99%
See 2 more Smart Citations